Model Altman Z-Score: Analisis Financial Distress Pada Perusahaan Penerbangan Yang Terdaftar Di Bursa Efek Indonesia - Idrawahyuni Idrawahyuni; Sri Rahayu; Reza Saputra (AkMen JURNAL ILMIAH, 2022)
This study aims to determine how to predict financial distress using the Altman Z-Score model for Indonesian airlines listed on the Indonesia Stock Exchange. The type of research used in this research is hypothesis testing with a quantitative approach. The population in this study are airlines registered with the Indonesian Stock Exchange. The samples in this study are PT Garuda Indonesia (Persero) Tbk and PT AirAsia Indonesia Tbk. The results showed that the financial performance of PT Garuda Indonesia (Persero) Tbk and PT AirAsia Indonesia Tbk were both predicted to experience financial distress, both PT Garuda Indonesia (Persero) TBk and PT AirAsia Indonesia Tbk both showing deteriorating financial performance or being in financial condition. distress in each period. However, when compared to the financial performance of these two companies between PT Garuda Indonesia (Persero) Tbk and PT AirAsia Indonesia Tbk from 2018 to 2020, PT Air Asia Indonesia showed a better performance, this can be seen from the Z Score generated by PT AirAsia. Indonesia Tbk is higher than the Z Score produced by PT Garuda Indonesia (Persero) Tbk, which means that PT Garuda Indonesia (Persero) Tbk has a higher prediction of bankruptcy than PT AirAsia Indonesia Tbk.